SoleMate: The Design and Development of a Smart Insole System (Journal of Medical Device Technology, 2024)
The SoleMate smart insole system, introduced in this study, addresses the growing prevalence of foot disorders and their associated complications. Foot disorders affect a substantial portion of the population, leading to foot pain and gait abnormalities. This research presents a low-cost, innovative solution that combines force-sensitive resistors (FSR), vibration motors, and a gyroscope sensor integrated with an ESP32 microcontroller. This system offers continuous monitoring of foot alignment and plantar pressure, along with the ability to provide alerts for abnormal foot alignment. By utilizing the Internet of Things (IoT) technology through the Blynk app, users can remotely monitor and control the device, enhancing its usability and potential for early detection and intervention in foot-related issues. While the SoleMate system shows promise, there is room for improvement, including reducing the system's size, adding sensors to enhance data collection, and improving the user interface. With its potential to improve foot health and overall well-being, the SoleMate system holds promise for healthcare professionals and individuals seeking effective foot-related problem management and prevention.
Keywords: Foot posture abnormalities; Plantar pressure; IoT wearables; Force-sensitive resistors (FSR); Gyroscope sensor; Graphical user interface (GUI); Smart insole